RELATIONSHIP BETWEEN C-REACTIVE PROTEIN AND IL-6 LEVELS AND EJECTION FRACTION IN HEART FAILURE PATIENTS AT ADAM MALIK HOSPITAL - Pratiwi, Harvinda Arya; Refli Hasan; Lubis, Masrul; Mardianto (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
Background: Heart failure (HF) is a progressive condition markedby anatomical and functional cardiac defects. Inflammation is amajor factor in HF development. While some research implies a linkbetween elevated CRP and IL-6 levels and lower ejection fraction(EF), the results are inconsistent. This study aims to evaluate therelationship between C-reactive protein, IL-6 levels, and EF in heartfailure patients.Method: This cross-sectional analytic observational study wasconducted at Adam Malik Hospital to assess the relationshipbetween CRP and IL-6 levels and left ventricular EF (LVEF) in HFpatients. Result: The findings showed no significant connection betweenCRP and LVEF (p=0.391), implying that CRP does not directlyreflect systolic dysfunction. Conversely, IL-6 levels have asubstantial inverse connection with LVEF (p=0.001), indicating agreater link between systemic inflammation and cardiacperformance. Conclusion: These findings underline the importance of amultimodal approach to HF care, including the use of inflammatorymarkers for risk classification in this population. While CRP maynot be as accurate a predictor of systolic dysfunction, IL-6 appearsto be more closely related to heart failure severity. Keywords: CRP, Ejection fraction, Heart failure, IL-6.